Epitope Mapping of Exposed Tegument and Alimentary Tract Proteins Identifies Putative Antigenic Targets of the Attenuated Schistosome Vaccine - Farias, Leonardo P.; Vance, Gillian M.; Coulson, Patricia S.; Vitoriano-Souza, Juliana; Neto, Almiro Pires da Silva; Wangwiwatsin, Arporn; Neves, Leandro Xavier; Castro-Borges, William; McNicholas, Stuart; Wilson, Keith S.; Leite, Luciana C. C.; Wilson, R. Alan (Frontiers in Immunology, 2021)
The radiation-attenuated cercarial vaccine remains the gold standard for the induction of protective immunity against Schistosoma mansoni. Furthermore, the protection can be passively transferred to naïve recipient mice from multiply vaccinated donors, especially IFNgR KO mice. We have used such sera versus day 28 infection serum, to screen peptide arrays and identify likely epitopes that mediate the protection. The arrays encompassed 56 secreted or exposed proteins from the alimentary tract and tegument, the principal interfaces with the host bloodstream. The proteins were printed onto glass slides as overlapping 15mer peptides, reacted with primary and secondary antibodies, and reactive regions detected using an Agilent array scanner. Pep Slide Analyser software provided a numerical value above background for each peptide from which an aggregate score could be derived for a putative epitope. The reactive regions of 26 proteins were mapped onto crystal structures using the CCP4 molecular graphics, to aid selection of peptides with the greatest accessibility and reactivity, prioritising vaccine over infection serum. A further eight MEG proteins were mapped to regions conserved between family members. The result is a list of priority peptides from 44 proteins for further investigation in multiepitope vaccine constructs and as targets of monoclonal antibodies.